ASSERING THE IMPACT OF MACROECONOMIC INDICATORS ON CORPORATE FINANCIAL PERFORMANCE: AN EMPIRICAL ANALYSIS IN ASIA - Fajri, Oisvira Maylani; Muhsyaf, Saipul Arni; Prasidya, Tusta Citta Ihtisan Tri (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
This study investigates the impact of macroeconomic indicators, specifically GDP growth and inflation, on corporate financial performance in selected ASEAN countries (Indonesia, Malaysia, the Philippines, Singapore, and Vietnam) from 2010 to 2022. Using data sourced from the OSIRIS database and the World Bank's World Development Indicators, the analysis focuses on three key financial metrics: Return on Assets (ROA), Net Profit Margin (NPM), and Market Capitalization (MC). Employing the Generalized Least Squares (GLS) method, the study addresses heteroskedasticity and autocorrelation in panel data, incorporating control variables such as Total Assets, Current Ratio, and Interest Coverage. Results indicate that GDP growth positively correlates with ROA and NPM, underscoring the importance of economic expansion for corporate efficiency and profitability. However, GDP growth does not significantly impact Market Capitalization, highlighting potential differences in market valuation dynamics. Inflation positively affects ROA and NPM, suggesting firms effectively manage inflationary pressures but does not significantly affect Market Capitalization. The findings provide actionable insights for financial managers, investors, and policymakers. Companies should integrate macroeconomic forecasts into business planning and adopt strategies to mitigate inflationary impacts. Future research directions include sector-specific analyses, longitudinal studies, and the incorporation of additional macroeconomic variables to deepen the understanding of these relationships.